Corrosion behavior of WC-Co coatings deposited by cold gas spray onto AA 7075-T6 - da Silva, F. S. [UNESP] (2018)
This work reports a morphological, mechanical, and corrosion resistance characterization of WC-12Co and WC-25Co coatings deposited by cold gas spray (CGS) onto AA 7075-T6 alloy. Cross-sectional images of the coatings revealed dense structures with low porosities. The coating thicknesses were 65 μm for WC-12Co and 118 μm for WC-25Co. XRD analysis showed that no fragile phases were formed in the coatings. SEM images and electrochemical results obtained after 700 h exposure to NaCl solution showed that WC-25Co exhibited better corrosion resistance performance. The WC-12Co and WC-25Co coatings withstood 1000 and 3000 h of salt fog spray test, respectively.